KAJIAN KOMUNIKASI ISLAM YASINAN DAN TABLILAN DALAM PANDANGAN MASYARAKAT - Muhtadin, Muhtadin (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
Communication   in Islam  is a religious proselytizing   (da wa) to invite people  to believe  and practice  Islamic faith (aqidah)  and  law  (Shari, a). Yasinan  means reciting  the verse  of Yasin together  either  in Friday  night  or certain nights  in mosques,  praying rooms,  or in any  hoeses  that  need  it. Tahlil means reciting the verse  of  "laa ilaaha illallaah  ",  Tahlilan  means  collectively  pray for  other people  such  as family.   relatives  or frends, etc.  Who have died  in order to gain the acceptance   of their deeds  and to receive Allah s forgiveness for  their faults and sins. In  writers  perspective,    the  Yasinan and  Tahlilan  are still debatable  in society.  Therefore  the writer  aims at analyz ing the argumentations   (dalil) or foundations   used by those who are pro  and con. In tum, society  hopefally  could understand  them. Additionally,   this study  hopefully  could give benefit for Islamic Umma in general  and the writer as well.